Inflammatory, Reactive, and Hypersensitivity Lesions Potentially Due to Metal Nanoparticles from Dental Implants and Supported Restorations: An Umbrella Review - Federica Di Spirito; Roberto Lo Giudice; Massimo Amato; Maria Pia Di Palo; Francesco D’Ambrosio; Alessandra Amato; Stefano Martina (Applied Sciences, 2022)
The present umbrella review aimed to assess the prevalence of cases diagnosed with lesions potentially due to Titanium (alloy) and other metal nanoparticles released from dental implants and implant-supported restorations, characterizing lesions’ macroscopic, imaging, and microscopic features. Secondary aims were to categorize the reported lesions as resembling or ascribable to peri-implant mucositis and peri-implantitis, reactive lesions of the peri-implant mucosa, or hypersensitivity reactions, and to evaluate their relationship with cases’, dental implants, and implant-supported restorations’ characteristics, and with the evidence of Titanium allergy. The study protocol, developed in advance and compliant with the PRISMA statement, was registered on PROSPERO (CRD42022354676). Systematic reviews were searched through the Web of Science, Scopus, MEDLINE/PubMed, Cochrane library databases, and the PROSPERO register until 19 August 2022; reference lists were also screened. Data from four systematic reviews of critically low/low quality (AMSTAR 2), one including a meta-analysis, were analyzed qualitatively. An overall prevalence of 16.9% of cases was estimated. Reported lesions resembled or were ascribable to peri-implant mucositis and peri-implantitis (55.17%), reactive lesions (17.22%), and hypersensitivity reactions (24.12%); no oral contact lichenoid lesions were described. Titanium allergy was hardly and heterogeneously investigated. Due to the severely incomplete data, no definitive conclusions could be drawn on the potential role of cases’ and implant characteristics and Titanium allergy on lesions onset, development, and treatment responsiveness.